6-Gingerol improves testicular function in mice model of chronic ulcerative colitis (2018)
The persistent inflammation and oxidative stress at the local site in ulcerative colitis reportedly extend to the testes via systemic circulation resulting in testicular dysfunction. The influence of 6-gingerol (6G), a phenolic compound isolated from Zingiber officinale, on colitis-mediated testicular dysfunction in mice was investigated in this study. Chronic ulcerative colitis was induced in mice using 2.5% dextran sulfate sodium (DSS) in drinking water for three cycles. Each cycle consisted of 7 consecutive days of exposure to DSS-treated water followed by 14 consecutive days of normal drinking water. 6G (100 mg/kg) or sulfasalazine (SZ; 100 mg/kg) was orally administered alone or in combination with DSS-treated water during the three cycles. SZ served as standard reference drug for colitis in this study. 6G significantly prevented the incidence of rectal bleeding, decrease in the body weight gain and colon mass index in DSS-exposed mice. 6G significantly prevented colitis-mediated decreases in luteinizing hormone, follicle-stimulating hormone and testosterone and decreases oxidative stress indices, pro-inflammatory cytokines and caspase-3 activity with concomitant augmentation of antioxidant enzymes activities, sperm characteristics, marker enzymes of testicular function and histoarchitecture in DSS-exposed mice. 6G exerted protective influence against ulcerative colitis-induced testicular damage via mechanisms involving its antioxidant and anti-inflammatory properties.